Hubungan Tingkat Solidaritas, Tingkat Konformitas Terhadap Tindakan Cancel Culture Penggemar K-POP di Indonesia - Evina Cahyani Budiaji (Universitas Sebelas Maret (UNS), 2024)
This study aims to explain the relationship between the level of solidarity, the level of conformity, and cancel culture actions among K-Pop fans in Indonesia. The theories used in this research are Emile Durkheim's theory of solidarity and Talcott Parsons' structural functionalism theory. The study employs a quantitative approach, survey method, and explanatory research design. Data were collected through online questionnaires from 96 K-Pop fans who follow the X account @starfess (population: 977,853 accounts). Data analysis techniques included data tabulation and correlation statistics tests (product-moment correlation test, partial product-moment correlation, and multiple correlation), assisted by the Statistical Package for the Social Sciences (SPSS) for Windows version 25.0. The results indicate a strong relationship between solidarity and conformity rxz = 0.777, a weak relationship between conformity and cancel culture actions rzy = 0.366, and a weak relationship between solidarity and cancel culture actions rxy = 0.330. The relationship between solidarity and cancel culture actions through conformity among K-Pop fans in Indonesia is rxy.z = 0.078, indicating an impure relationship. Collectively, solidarity, conformity, and cancel culture actions show a low relationship Ry.xz = 0.375. These findings demonstrate that Emile Durkheim's theory of solidarity and Talcott Parsons' structural functionalism theory effectively explain the interconnectedness of these three variables.